A comparative study of low dose magnesium sulphate therapy with standard pritchard’s regime in the management of eclampsia - Mohanapu, Swarnalatha; Raveendran, Sajeethakumari; Murugaiah, Yogashalini; Sen, Maitrayee (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Eclampsia is one of the most serious and potentially catastrophic complications of pregnancy and still remains a common cause of maternal and perinatal mortality and morbidity in India. Magnesium sulphate is the main stay of treatment in eclampsia and imminent eclampsia. As the margin of safety between therapeutic and toxic levels of magnesium sulphate is narrow, monitoring the serum magnesium levels to assess the criticality of situation is an uphill task in our hospitals, there is a need for modification of dosage of magnesium sulphate in tropical countries. This study compared the efficacy and toxicity of low dose magnesium sulphate regime with the standard pritchard’s regime in eclampsia. Methods: 50 cases of eclampsia were treated with low dose magnesium sulphate and 50 cases of eclampsia with standard Pritchard’s regime. The recurrence rate of convulsions and magnesium toxicity were analysed. Results: It was observed that with low dose magnesium sulphate regime, convulsions were controlled in 90% of the cases. With standard pritchard’s regime convulsions were controlled in 96% of patients. The maternal and perinatal mortality and morbidity were comparable in both groups. Conclusions: Low dose magnesium sulphate therapy is as effective as Pritchard’s regime for controlling convulsions in eclampsia.